Partial virological response to three different nucleotide analogues in naive patients with chronic hepatitis B - (:unkn) unknown (ELSEVIER SCIENCE BV, 2014)
BACKGROUND: The definition of partial virological response (PVR) was proposed because of its clinical relevance. PVR relates to subsequent therapeutic failure which results in the modification of the regimen. Whether this rationale can be applied to all nucleotide analogues (NA) is not clear. This study was undertaken to analyze PVR influence on therapeutic outcomes during lamivudine, entecavir or tenofovir monotheraphy in NA-naive patients with chronic hepatitis B in routine clinical practice. METHODS: We retrospectively analyzed 150 NA-naive patients with chronic hepatitis B. These subjects received lamivudine, entecavir or tenofovir monotherapy between February 2001 and July 2013. RESULTS: Sixty-nine patients were treated with lamivudine, 35 with entecavir, and 46 with tenofovir. The median therapeutic duration was 19.5 (6-147) months. PVR rates at 24 weeks were similar among three NAs (lamivudine 33.3%, entecavir 35.0%, tenofovir 32.4%, P=0.981). For all three NAs, patients with a higher baseline viral load or HBeAg-positive status had a higher serum viral positive rate tested by polymerase chain reaction at week 24 and 48. Cumulative probability of virological breakthrough (VBR) for patients treated with lamivudine was 67% at 5 years, and PVR at 24 weeks was the independent risk factor for VBR (HR: 3.09; 95% CI: 1.09-8.74; P=0.034); also lamivudine treated patients older than 50 years seemed to have a tendency for VBR (HR: 2.80; 95% CI: 0.99-8.18; P=0.052). A majority of entecavir and tenofovir partial responders achieved and maintained virological response with prolonged monotherapy, except one entecavir treated patient who experienced VBR due to resistance mutations. CONCLUSIONS: Management strategy for lamivudine treatment should include adaptation of regimen according to PVR as an on-treatment response parameter due to its relation with unacceptably high VBR probability. Similar conclusion should not be directly related to entecavir or tenofovir treatment.
Keywords: partial virological response; lamivudine; entecavir; tenofovir; therapeutic outcome; TENOFOVIR DISOPROXIL FUMARATE; VIRUS GENOTYPE-D; SERUM HBV DNA; LAMIVUDINE THERAPY; VIRAL LOAD; HEPATOCELLULAR-CARCINOMA; ENTECAVIR TREATMENT; ACUTE EXACERBATION; NATURAL-HISTORY; LIVER-DISEASE